"The effect of using the gamification strategy in reducing mathematics anxiety among second-grade intermediate students." (Journal of the College of Basic Education, 2025)
The aim of this research is to investigate the effect of the gamification strategy in reducing mathematics anxiety among second-grade intermediate students. The research sample consisted of (63) male students enrolled in the second semester of the academic year (2024–2025). Al-Dhad Intermediate School for Boys, affiliated with the General Directorate of Education in Baghdad / Al-Rusafa Second, was selected. Through random assignment, Class (B) was chosen as the experimental group, which was taught using the gamification strategy (30 students), while Class (C) was selected as the control group, which was taught using the traditional method (33 students). The two groups were equalized on the following variables: intelligence, chronological age in months, prior knowledge in mathematics, previous academic achievement in mathematics, and parents' educational level. The Mathematics Anxiety Scale, originally developed by Moh Rustam Mohd Rameli (2016), was adopted and adapted to fit the local environment. The validity and reliability of the scale were confirmed. After completing the experiment, the Mathematics Anxiety Scale was administered to both groups. Data were collected and analyzed using appropriate statistical methods. The results revealed a statistically significant difference between the experimental and control groups in mathematics anxiety levels, favoring the experimental group. In light of these findings, it is recommended to adopt and implement the gamification strategy across various educational stages due to its proven effectiveness in reducing students’ mathematics anxiety. The results also indicated that gamification contributes to promoting positive attitudes toward mathematics by creating a more engaging and interactive learning environment, thus reducing students’ feelings of stress and frustration typically associated with traditional mathematical tasks. Therefore, the widespread use of this strategy could have a broad positive impact in alleviating anxiety not only in mathematics but also in other academic subjects.